Pasteurella sp. associated with fatal septicaemia in six African elephants - Foggin, Chris M.; Rosen, Laura E.; Henton, Marijke M.; Buys, Angela; Floyd, Toby; Turner, Andrew D.; Tarbin, Jonathan; Lloyd, Antony S.; Chaitezvi, Columbas; Ellis, Richard J.; Roberts, Helen C.; Dastjerdi, Akbar; et al. (Nature communications, 2023)
The sudden mortality of African elephants ( Loxodonta africana ) in Botswana and Zimbabwe in 2020 provoked considerable public interest and speculation. Poaching and malicious poisoning were excluded early on in the investigation. Other potential causes included environmental intoxication, infectious diseases, and increased habitat stress due to ongoing drought. Here we show evidence of the mortalities in Zimbabwe as fatal septicaemia associated with Bisgaard taxon 45, an unnamed close relative of Pasteurella multocida . We analyse elephant carcasses and environmental samples, and fail to find evidence of cyanobacterial or other intoxication. Post-mortem and histological findings suggest a bacterial septicaemia similar to haemorrhagic septicaemia caused by P. multocida . Biochemical tests and 16S rDNA analysis of six samples and genomic analysis of one sample confirm the presence of Bisgaard taxon 45. The genome sequence contains many of the canonical P. multocida virulence factors associated with a range of human and animal diseases, including the pmHAS gene for hyaluronidase associated with bovine haemorrhagic septicaemia. Our results demonstrate that Bisgaard taxon 45 is associated with a generalised, lethal infection and that African elephants are susceptible to opportunistically pathogenic Pasteurella species. This represents an important conservation concern for elephants in the largest remaining metapopulation of this endangered species. A series of unexplained elephant mortalities occurred in northwest Zimbabwe in 2020. Here the authors show that six elephants died of bacterial septicaemia associated with a little-reported Pasteurella species.